2016
DOI: 10.1016/j.str.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

KDM2B Recruitment of the Polycomb Group Complex, PRC1.1, Requires Cooperation between PCGF1 and BCORL1

Abstract: SUMMARY KDM2B recruits H2A-ubiquitinating activity of a non-canonical Polycomb Repression Complex 1 (PRC1.1) to CpG islands, facilitating gene repression. We investigated the molecular basis of recruitment using in vitro assembly assays to identify minimal components, subcomplexes and domains required for recruitment. A minimal four-component PRC1.1 complex can be assembled by combining two separately isolated subcomplexes: the DNA binding KDM2B/SKP1 heterodimer and the heterodimer of BCORL1 and the core PRC1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 27 publications
5
60
0
1
Order By: Relevance
“…However, in leukemic cells we find that USP7 inhibition not only leads to reduced H2AK119ub but also induces loss of PRC1.1/KDM2B binding as a result of complex disassembly, suggesting that KDM2B-PCGF1-BCOR/L1/SKP1 interactions might be needed for targeting. This is in agreement with data that suggest that dimerization of PCGF1 and BCOR(L1) is required for binding to KDM2B and recruiting PRC1.1 to the chromatin [64].…”
Section: Discussionsupporting
confidence: 93%
“…However, in leukemic cells we find that USP7 inhibition not only leads to reduced H2AK119ub but also induces loss of PRC1.1/KDM2B binding as a result of complex disassembly, suggesting that KDM2B-PCGF1-BCOR/L1/SKP1 interactions might be needed for targeting. This is in agreement with data that suggest that dimerization of PCGF1 and BCOR(L1) is required for binding to KDM2B and recruiting PRC1.1 to the chromatin [64].…”
Section: Discussionsupporting
confidence: 93%
“…It appears that the huge megaDalton sized protein assemblies build up in a well-defined, step by step process. First, different sub-complexes are formed, as described in the case of ncPRC1.1 [357]. It was found that KDM2B/SKP1 heterodimer can only bind to PCGF1 RAWUL domain after the formation of a PCGF1/BCORL1 heterodimer.…”
Section: The Assembly Of Ncprc1 Subunits Is Still Under Debatementioning
confidence: 99%
“…It was found that KDM2B/SKP1 heterodimer can only bind to PCGF1 RAWUL domain after the formation of a PCGF1/BCORL1 heterodimer. The BCORL1 PUFD domain preceding the RAWUL domain produces the extended interface only after heterodimer formation for interaction of the preformed KDM2B/SKP1 sub-complex [357]. Subsequently, the complex grows even larger after contacting the RING1 (or RNF2) and RYBP/YAF2 module.…”
Section: The Assembly Of Ncprc1 Subunits Is Still Under Debatementioning
confidence: 99%
“…Variant PRC1 accessory proteins can also provide unique functionality to the PRC1 complexes. For example, the H3K36me2 demethylase, KDM2, interacts with the variant BCOR complex and recruits the complex to CPG islands [32, 77, 78]. Beyond ubiquitination, PRC1 complexes repress gene activity by chromatin compaction [20, 33, 92].…”
Section: Polycomb H2a Ubiquitinationmentioning
confidence: 99%
“…Besides skeletal transformations, Asxl1 −/− mice exhibit microphthalmia, craniofacial dysmorphisms and myelodysplasia but have not been described as microcephalic [33, 7577]. Asxl2 −/− mice showed enlarged hearts with interstitial fibrosis and cardiomyocyte disarray and do not exhibit macrocephaly [73, 78]. This discrepancy in brain size phenotypes between mice and humans is an interesting observation that warrants further analysis, as the role for PR-DUB function in brain development has not yet been described.…”
Section: H2aub1 Deubiquitination Syndromesmentioning
confidence: 99%